COMPANY PROFIT GROWTH AND QUICK RATIO ON STOCK PRICE: AN EVIDENCE OF OIL AND GAS COMPANIES IN INDONESIA STOCK EXCHANGE - Marbun, Ramlon; Sihotang, Ronny Buha (2021)
This study analyzes the effect of Company Profit Growth and Quick Ratio on Stock Price on oil and gas companies listed on the Indonesia Stock Exchange. The sample used in this study was 9 companies on 2014-2019, so that 45 research samples were obtained. In this study, Company Profit Growth is measured using the percentage of the profit growth proxy and Stock Price using the percentage of the current stock price and last year stock price. Based on research, simultaneously, Profit Growth and Quick Ratio have a significant effect on Stock Price. While partially the Profit Growth has no relationship on the Stock Price and Quick Ratio has no effect on the Stock Price. Profit Growth and Quick Ratio contributed 3.5% to Stock Price.